Drosophila Adducin facilitates phase separation and function of a conserved spindle orientation complex - Parra, Amalia S.; Moezzi, Cameron A.; Johnston, Christopher A. (Frontiers in Cell and Developmental Biology, 2023)
Asymmetric cell division (ACD) allows stem cells to generate differentiating progeny while simultaneously maintaining their own pluripotent state. ACD involves coupling mitotic spindle orientation with cortical polarity cues to direct unequal segregation of cell fate determinants. In Drosophila neural stem cells (neuroblasts; NBs), spindles orient along an apical-basal polarity axis through a conserved complex of Partner of Inscuteable (Pins; human LGN) and Mushroom body defect (Mud; human NuMA). While many details of its function are well known, the molecular mechanics that drive assembly of the cortical Pins/Mud complex remain unclear, particularly with respect to the mutually exclusive Pins complex formed with the apical scaffold protein Inscuteable (Insc). Here we identify Hu li tai shao (Hts; human Adducin) as a direct Mud-binding protein, using an aldolase fold within its head domain (HtsHEAD) to bind a short Mud coiled-coil domain (MudCC) that is adjacent to the Pins-binding domain (MudPBD). Hts is expressed throughout the larval central brain and apically polarizes in mitotic NBs where it is required for Mud-dependent spindle orientation. In vitro analyses reveal that Pins undergoes liquid-liquid phase separation with Mud, but not with Insc, suggesting a potential molecular basis for differential assembly mechanics between these two competing apical protein complexes. Furthermore, we find that Hts binds an intact Pins/Mud complex, reduces the concentration threshold for its phase separation, and alters the liquid-like property of the resulting phase separated droplets. Domain mapping and mutational analyses implicate critical roles for both multivalent interactions (via MudCC oligomerization) and protein disorder (via an intrinsically disordered region in Hts; HtsIDR) in phase separation of the Hts/Mud/Pins complex. Our study identifies a new component of the spindle positioning machinery in NBs and suggests that phase separation of specific protein complexes might regulate ordered assembly within the apical domain to ensure proper signaling output.